Association of Glomerular Filtration Rate With Slow Coronary Flow in Patients With Normal to Mildly Impaired Renal Function. (October 2014) - Akin, Fatih; Celik, Omer; Ayça, Burak; Yalçın, Ahmet Arif; Altun, Ibrahim; Köse, Nuri
We evaluated the association between estimated glomerular filtration rate (eGFR) and slow coronary flow (SCF) in patients with normal to mildly impaired renal function; 211 patients with angiographically proven SCF and 219 controls were studied. Patients were categorized based on the angiographic findings as with or without SCF. We used the Modification of Diet in Renal Disease equation to calculate eGFR. The frequency of mildly decreased eGFR, serum uric acid levels, and eGFR was higher in the SCF group. Patients with mildly impaired renal function had higher thrombolysis in myocardial infarction frame counts in 3 major coronary arteries. In logistic regression analysis, uric acid (odds ratio [OR] = 1.323, 95% confidence interval [CI] = 1.109-1.572, P = .002) and eGFR (OR = 0.972, 95% CI = 0.957-0.987, P < .001) were independent correlates of SCF. In conclusion, eGFR was significantly correlated with SCF in patients with normal to mildly impaired renal function.